EFFORTS TO BUILD ENTREPRENEURSHIP CHARACTERS THROUGH THE LIFE SKILL TRAINING PROGRAM - Udin Nasrudin; Nandang Rukanda (IKIP Siliwangi Bandung, 2020)
This research's background is the improvement of the quality of the younger generation, especially foster children who live in orphanages, to have an entrepreneurial spirit as a provision for their life so that they can live independently. To live independently, they must be equipped with knowledge and skills as essential capital for entrepreneurship because, so far, most of them are life-oriented to work or become employees. Therefore it is necessary to change their mindset to become successful entrepreneurs. The research objective is to find out how the managers of the Muhammadiyah Sumur Bandung Orphanage's efforts in building the entrepreneurial spirit of foster children through life skills training programs. Researchers used interview techniques with qualitative descriptive methods to obtain information from sources. The sample in this study was an orphanage manager, one tutor, and two foster children. The results of research at the Muhammadiyah Sumur Bandung Orphanage are the efforts of the managers of the Muhammadiyah Sumur Bandung Orphanage in building the entrepreneurial spirit of foster children through life skills training programs that have gone well seen from the achievement of improving the quality of alumni who are entrepreneurial. The foster children's entrepreneurial ability grows through the manager's efforts to provide life skill training programs at the Muhammadiyah Sumur Bandung Orphanage. The orphanage manager's efforts are very decisive in increasing the ability of foster children to have an entrepreneurial spirit.